PENGEMBANGAN MEDIA PEMBELAJARAN KOMK DIGITAL BERBASIS NILAI KARAKTER PADA MATERI SISTEM RESPIRASI UNTUK SISWA KELAS XI SMA - Yuliana, Elvira; Natalina. L, Mariani; Arnentis, Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:The 21st century generation is a generation that is faced with technological advances, especially the digital world. Meanwhile, technological advances do not rule out the possibility of deviant actions being carried out by students who violate norms and have negative characters. This is a challenge for teachers to apply more digital media by instilling character values in learning, so that they are more relevant to students' lives. One of them is digital comic media based on character values. This study aims to develop digital comic media based on quality character values in the Human Respiratory System material. This research was conducted at the Biology Education Study Program, FKIP UNRI, SMAN Plus Riau Province and MAN 1 Pekanbaru in March 2021 - October 2021. The type of research carried out was Research and Development with the ADDIE model. The instruments used are validation sheets and response questionnaires. The validation results obtained an average value of 3.83 very valid categories. The results show that digital comics based on character values on the human respiratory system material have been successfully developed and are of good quality and are suitable for use as learning media.Key Words : Comic, Digital, Human Respiratory System